PENGARUH FILTER AKTIF DENGAN PENGATURAN DAYA REAKTIF TERHADAP EFISIENSI TRAFO BERBASIS SIMULINK - Satriya Dhinata, IK; Maharta Pemayun, AAG; Manuaba, IB Gede (Jurnal SPEKTRUM; Vol 8 No 4 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i04.p17, 2022)
Harmonic distortion usually occurs due to the operation of excessive non-linear electrical loads, this distortion can be reduced by utilizing an active harmonic filter which can usually be adjusted for reactive power on the filter. In this study, an analysis of reactive power settings on the active filter was carried out to determine the efficiency value obtained by following the IEEE 519 - 2014 THDi standard value of 8% for each phase. The results of the analysis of the smallest reactive power setting but exceeding the transformer efficiency value when the existing condition meets the IEEE 519 - 2014 standard is 40 % with the THDi value for the R phase = 7, 54%, S = 7,74%, and T = 7, 37% obtained an efficiency value of 96, 31%.